Gender and citizenship in Peru: new scenarios and research agendas - Vincent, Susan (2022)
The way in which the state recognizes citizenship with respect to gender roles in Peru has been out of step with actual gender practices. For most of the period since Spanish colonization, the average citizen has been officially designated or imagined as a heterosexual male. Over the last half century, women have come to occupy independent citizenship roles in ways that compel them to conform to a model of maternal morality and domestic responsibility. In today's neo-extractivist economy, with the strong public voice of social conservatism and entrenched political corruption, this poses behavioral constraints and the risk of indebtedness. Very few policy changes have been directed at transforming male gender roles or targeting LGBTI citizens. I request more research on the implications of this situation to support the movements that fight so that all Peruvians, regardless of their gender identity or sexuality, live a full life.